A diachronic exploration on the coverage of the top three Philippine daily broadsheets’ editorial of the fifth republic presidents’ discourses on development and poverty in their SONAs. - Lopez-Hernando, Leonor C.
This dissertation examines the editorials of the Philippines' three largest circulation broadsheets covering the Fifth Republic presidents' notions of development and poverty in the periodic State of the Nation Address (SONA). Guided by a rights-based approach, integrating the MDGs, SDGs, and PDPs, the levels of development, and reasons of poverty (Burkey, 1993), Pan and Kosicki's (1993) framing devices and practices shared by editorial board members during the in-depth interviews, the 138 editorial articles were then analyzed. A mixed-methods approach was employed to diachronically evaluate the messages in the editorials from 1987 to 2021. Thus, throughout and across regimes, there was no shift in the discourses of development and poverty. The editorialization of these discourses by the publications also reflects the relationship between the press and the president. Manila Bulletin and The Philippine Star are more like propaganda machines in which their editorials serve simply to praise the president's agendas in short articles, while the Philippine Daily Inquirer endeavors to present criticism in articles with the longest length. Development is primarily viewed at the macro level and as debt-driven development, whereas the solution to poverty is emphasized as poverty reduction initiatives, all mandated by the UN, World Bank, and IMF for debt-ridden Third-World nations like the Philippines.